RANCANG BANGUN APLIKASI DRIVE TEST BERBASIS ANDROID UNTUK MENGUKUR KUAT JARINGAN 3G DENGAN PENGUKURAN IDLE MODE - ., Guntoro (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Drive test is one of the first steps in the process of network optimization that aims to collect data measurements in less optimal areas. Drive test requires many tools such as laptop with TEMS software installed, mobile phone, data cable, GPS and usually a car. This study aims to design android applications that can be used to do drive test with idle mode method without requiring many tools and the results of drive test data analysis can be used for network optimization in less optimal areas. The result of data analysis of drive test application named SignalTrack shows that RSCP value on Jl. Prof. M. Yamin is still bad because the spot ratio is very good, which is only 55.74% while usually each provider targets 95% threshold. The comparison of drive test application by using NEMO software if being seen from the drawing and table result is similar, and for the level of accuracy of SignalTrack is also not much different from NEMO. Â  Keywords: Drive Test, KPI, Idle Mode, SignalTrack.